THOUGHTS OF SANTRI: Polite Culture in Islamic Boarding Schools - Hastuti, Anita (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Islamic boarding schools are educational institutions based on Islamic values, in their teaching system emphasizing the formation of Islamic character, one of which is polite and friendly behavior. Therefore, in the daily life of students, they are always required to behave politely towards others, it has even become a culture of interaction. This study aims to describe the polite behavior of students in the Islamic boarding school environment. This research was conducted at the Nurul Hidayah Islamic boarding school, Bogor Regency. Research data were obtained from observations by taking notes, seeing, hearing, and interacting. The number of students who became the source of observation was fifty people. This study used a qualitative approach with descriptive analysis. The results of the study show that in interacting and communicating, the students get used to behaving politely and politely in speaking. So that the expression that comes out when communicating is humility, gentleness and mutual respect for the opinions of others.